(untitled) (Revista Argentina de Musicología, 2018)
This is the original text read at the "Mozart and South America Days” (Salzburg, October 27/28. 2003). It focusses on the Mozartvariationen (1991 ) by Gerardo Gandini (Buenos Aires, 1936). The piece is based on a compositional procedure Gandini has often used during the past decades which refers to an “objet trouvé”. In this case, the found object is the set of variations for piano Ah vous dirai-je, Maman, KV 265 (1776), by W. A. Mozart. This material undergoes different processes of deconstruction and defragmentation. reaching a kind of “musicophagy” that goes through the European music tradition of the past "to escape from the stereotypes of cotemporary music”, as expressed by the composer.